Protein level and lysine supplementation of diets for weaned pigs - G L Allee; B A Koch; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1975)
Seventy-two pigs, 30 days old averaging 17 pounds initially, were used to evaluate lysine additions to 16 and 18 percent protein fortified corn-soybean meal diets. Adding 0.1% or 0.2% L-lysine to the 16% protein diet increased weight gains. Gain and efficiency of pigs fed the 16% protein diet supplemented with 0.2% L-lysine were similar to that of pigs fed the 18% protein corn-soybean meal diet. Adding lysine to the 18% protein diet improved neither gains nor feed efficiency of pigs weaned at four weeks of age.; Swine Day, Manhattan, KS, November 13, 1975
Keywords: Swine day; 1975; Kansas Agricultural Experiment Station contribution; no. 505; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Protein; Lysine; Weaned pigs